Analisis Pengelolaan Keuangan Pribadi Wanita Pedesaan (Desa Gebanganom Wetan Kecamatan Kangkung Kabupaten Kendal) - Evy Fauziah; Nanang Yusroni; Hasan Hasan (AKSES: Jurnal Ekonomi dan Bisnis, 2021)
This article analyzes the influence of spiritual intelligence, the lifestyle of hedonism and financial knowledge on personal finance management housewives in the Village Gebanganom Wetan Kecamatan Kangkung Kendal. Methods of data collection as much as 94 housewives with the technique of proportional stratified random sampling, data analysis including the validity test, reliability test, normality test, multicollinearity test, hetereskedastisitas, autocorrelation test, multiple linear regression analysis, t test, F test and coefficient of determination (R2) with the software eviews 10. The value of multiple linear regression Y = 9,860 + 0,290X1 + 0,162X2 + 0,467X3 + e , t test shows that financial knowledge significant positive effect on financial management personal, spiritual intelligence and hedonistic lifestyle has no significant effect on personal financial management. F test results showed that the three variables simultaneously affect the management of personal finance. The coefficient of determination (R2) shows the results 0,181 which means 18,1% spiritual intelligence, the lifestyle of hedonism and knowledge of the financial effect on the financial management of the personal, the rest of 81.9% influenced by other factors outside the research.Keywords : spiritual Intelligence, hedonistic lifestyle, financial literacy, personal finance Management, housewife